Safety assessment of the implementation of enhanced-algorithms at ukrainian NPPs - Glushenkov, Roman Sergeevich (Eastern-European Journal of Enterprise Technologies, 2012)
This article contains comparison of analytical analysis of Enhanced-algorithms to control power distribution in active zone with algorithm that was used before. The result of calculation of four-year fuel-campaign with using program code BIPR-7A is produced